The Effect Of The Covid 19 Pandemic On The Implementation Of The School Dental Health Programme (UKGS) In Semarang Regency In 2021 - Sri Rahayu; Ameilia Vidyaninggar (Soepra Jurnal Hukum Kesehatan, 2022)
Abstract:  Puskesmas is a first-level health service facility whose task is to provide promotive, preventive and curative services. Health services at Puskesmas include Community Health services and Individual Health Services. School Dental Health Programme   (UKGS) is a community health service related to dental and oral health that targets primary school-age children. The Covid-19 pandemic makes many problems that have hindered the implementation of this program. Descriptive research is held to know the implementation of UKGS in Semarang Regency during a pandemic, especially in 2021, and the factors that influence it. Data was collected from monthly reports and analyzed by qualitative methods, referring to the regulation and result of discussion during evaluation activities with dental and oral health programmers at Puskesmas. Data shows that only 50 % of elementary school students had to dental examination, and only 12,5 % of students get dental treatment. The dental health worker spent more time controlling covid 19.  Prevention programme to decrease Covid 19 transmission and learning  system online is the main obstacle. There are some Puskesmas with good performance who utilize technology information to hold UKGS. Technology information is an alternative for implementing on UKGS programme, when pandemic covid 19 is still ongoing, or when it has been declared an endemic disease. So collaboration work needed to involve the health district office, school and Puskesmas.A legally binding regulation form is needed, like regulation or decree of the health minister. The Circular Letter of Health Minister, Republik of Indonesia Number HK.02.01/303/2002 concerning the Implementation of Health Services through the Utilization of Information and Communication Technology in the Context 0f Preventing the Spread of Corona Virus Disease 2019 has no binding legal force as hierarchy regulation the contained in Law number 12 0f 2011 concerning the Establishment of Law regulation. The Health Office of Semarang regency, should compile technical instructions concerning School Dental Health Programme   (UKGS ) during pandemic covid 19 and socialized it to improve the achievement of UKGS.Keywords: UKGS, Pandemic Covid 19, Semarang Regency. Abstrak: Puskesmas merupakan fasilitas pelayanan kesehatan tingkat pertama yang bertugas memberikan pelayanan promotif, preventif, dan kuratif. Pelayanan kesehatan di Puskesmas meliputi pelayanan Kesehatan Masyarakat dan Pelayanan Kesehatan Perorangan. Program Kesehatan Gigi Sekolah (UKGS) merupakan pelayanan kesehatan masyarakat terkait kesehatan gigi dan mulut yang menyasar anak usia sekolah dasar. Pandemi Covid-19 membuat banyak masalah yang menghambat pelaksanaan program ini.Penelitian deskriptif diadakan untuk mengetahui pelaksanaan UKGS di Kabupaten Semarang pada masa pandemi khususnya tahun 2021, dan faktor-faktor yang mempengaruhinya. Data dikumpulkan dari laporan bulanan dan dianalisis dengan metode kualitatif, mengacu pada peraturan dan hasil diskusi selama kegiatan evaluasi dengan programmer kesehatan gigi dan mulut di Puskesmas. Data menunjukkan bahwa hanya 50% siswa sekolah dasar yang melakukan pemeriksaan gigi, dan hanya 12,5% siswa yang mendapatkan perawatan gigi. Tenaga kesehatan gigi lebih banyak menghabiskan waktu mengendalikan covid 19. Program pencegahan penularan Covid 19 dan sistem pembelajaran online menjadi kendala utama. Ada beberapa Puskesmas yang kinerjanya baik yang memanfaatkan teknologi informasi untuk menyelenggarakan UKGS. Teknologi informasi menjadi salah satu alternatif pelaksanaan program UKGS, saat pandemi covid 19 masih berlangsung, atau sudah dinyatakan endemis penyakit. Sehingga diperlukan kerja sama yang melibatkan dinas kesehatan, sekolah dan Puskesmas.Diperlukan suatu bentuk peraturan yang mengikat secara hukum, seperti peraturan atau keputusan menteri kesehatan. Surat Edaran Menteri Kesehatan Republik Indonesia Nomor HK.02.01/303/2002 tentang Penyelenggaraan Pelayanan Kesehatan Melalui Pemanfaatan Teknologi Informasi dan Komunikasi Dalam Rangka Pencegahan Penyebaran Corona Virus Disease 2019 tidak mempunyai kekuatan hukum mengikat sebagai pengaturan hierarki yang tertuang dalam Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan. Dinas Kesehatan Kabupaten Semarang, hendaknya menyusun petunjuk teknis tentang Program Kesehatan Gigi Sekolah (UKGS) di masa pandemi covid 19 dan mensosialisasikannya untuk meningkatkan pencapaian UKGS.Kata kunci: UKGS, Pandemi Covid 19, Kabupaten Semarang.